Ambush and Meteorology in the Noble Qur’an: A grammatical semantic study (Raparin Journal of Humanities (RJH), 2023)
It became clear to me that the terms stalking and stalking in the Holy Qur’an came with two different connotations from each other, and even the forms in which these two words appeared were grammatically different. Indeed, stalking is mentioned in the past tense, present tense, imperative, noun and infinitive as well, and it is frequently used in the Holy Qur’an, in When I found (Rasd) and its derivatives are few in roses, and its uses are more named. Also, stalking came in some verses of legislative provisions, and that stalking has a meaning more than the meaning of waiting, and it is the most common meaning because it falls in the commendable and unpleasant matter. This difference is essential between them, because the forces of stalking are stronger than the forces of stalking.